The Concept Of Anti-Corruption Education Leadership In The Era Of Society 5.0 In An Islamic Perspective - Dessy Afriyani; Harry Soeratin (Zona Education Indonesia, 2023)
The millennial generation in the Society 5.0 era has different characteristics from previous generations. Millennials tend to always want to find out about the times. They search, learn and work in an innovative environment that relies heavily on technology to make changes in various aspects of their lives. In terms of providing input to this generation, a special strategy is needed. Similarly, anti-corruption education requires a special approach in order to provide them with a targeted understanding. Furthermore, a learning method that suits the character of the millennial generation is needed. Leadership plays a very important role in the anti-corruption education process for this millennial generation. Good and successful leadership will certainly be mentioned as the cause of good consequences in various results according to the scope of leadership. The author will present the concept of anti-corruption education leadership for the millennial generation in the Society 5.0 era through an Islamic perspective.